P442 Strictureplasty for Crohn's disease of the small bowel in the biological era: long-term outcomes and risk factors for site specific recurrence. (25th January 2019) - Rottoli, M; Manzo, C A; Tanzanu, M; Rizzello, F; Gionchetti, P; Poggioli, G
Abstract: Background: Patients affected by Crohn's disease (CD) often require multiple surgeries and are at higher risk of short bowel syndrome. While bowel-sparing techniques should still have an indication in these patients, a considerable reduction of the use of strictureplasty has been observed, especially since the introduction of biological drugs. Methods: Patients undergoing strictureplasty for small bowel CD from 2002 were included. Risk factor for recurrence of CD were analysed through a multilevel logistic regression analysis, considering the hierarchical structure of the data. Level-2 variables were related to patient, level-1 to strictureplasty. A model without predictors was run to calculate the intraclass correlation coefficient to evaluate the degree of homogeneity of the outcome within patients; an intermediate model adding level-1 and level-2 variables and testing all intra-level interactions was subsequently performed. The estimated residual standard deviation and the estimated residual intraclass correlation of random-intercept logistic model were calculated. All p values refer to two-tailed tests of significance. A p -value of < 0.05 was considered significant. Results: A total of 266 patients were included in the study. Overall, 718 strictureplasties were performed. Median follow-up time was 96 months (6–209). Site specific recurrence rate was 1.6% at 2 years, 12.7% at 5 years, and 25.7% at 10 years. Conclusions: Strictureplasty is a safe procedure and is correlated with acceptable recurrence-free rates also after a very long follow-up time. Despite nonconventional strictureplasties are associated with a significantly higher risk of site specific relapse, whenever possible a bowel sparing technique should be performed, especially in the presence of long strictures. In case of a recurrence of a previous anastomosis, a resection should be preferred. The use of biologics after surgery identifies patients at higher risk of recurrence. The effect of biological drugs on long-term outcome after bowel sparing technique should be assessed in future prospective trials.